THE EFFECT OF GIVING DRAGON FRUIT PEEL JUICE THROUGH DRINKING WATER ON QUAILS EGG PRODUCTIONS - C. H, Ke; Umiarti, A.T.; Dewi, G. A. M. K. (Jurnal Peternakan Tropika, 2023)
This study aims to determine the effect of giving dragon fruit peel juice through drinking water on the production of quail eggs. The design used was Completely Randomized Design (CRD) consisting of 4 treatments and 4 replications where each replication consisted of 5 quails. The treatments were drinking water without dragon fruit peel juice (A), drinking water given 3% dragon fruit peel juice (B), drinking water given 4% dragon fruit peel juice (C), drinking water given 5% fruit peel juice dragon (D). The variables observed included ration consumption, drinking water consumption, egg weight, daily egg production (HD) and ration conversion. The results showed that drinking water given 5%(D) dragon fruit peel juice resulted higher egg weight and low ration conversion it was significantly different (P<0.05) with 0%(A), 3%(B) and 4% treatment, while drinking water with a low level of 3%, 4%, and 5% could result in feed consumption, drinking water consumption, and daily egg production which were not significantly different (P>0.05) than quail fed with drinking water without dragon fruit peel juice 0% (A). Based on the results of the study, it can be concluded that giving drinking water given 3%, 4% and 5% dragon fruit peel juice has the same effect on ration consumption, drinking water consumption and daily egg production but 5% dragon fruit peel juice gave inccreased egg weight and dekreased Feed Convertion Ratio of quail.